Javanese Royal Kingdom Addressing System in Kethoprak - Icha Latifa Hanum (Deskripsi Bahasa, 2021)
Javanese language in the context of the royal kingdom has a complex system. This hierarchy-based speech slowly disappears as this system is declined nowadays in order to national and international politics (Blust, 2013). However, the pure form of Javanese language system, especially in the term of kingship, remains and is reflected in folk art as the society's response to its existence. Kings, as Weber (1978:294) argues, have to rely on the basis of legitimacy believed by their subordinates or followers as a way that explains their kingships in order to legitimize their rule as kings or leaders over their realms. Thus, this paper tries to briefly reveal the language and power relations in Javanese kingship by examining the system of addressing terms in kethoprak. Through critical sociolinguistics study of kethoprak discourse, the complex Javanese language system that is influenced by the royal kingdom and its structure are revealed. Overall, the use of addressing terms in the royal kingdom context was found to be dynamic, break and complement the related previous studies.